Massive small bowel resections - Pereyra, Odel Abisab; del Campo, Alberto; Knobel, Alejandro; de Mattos, Alfredo; Fernández, Miguel A; Gravina, F (Cirugía del Uruguay, 1972)
This work obtained the Wyeth Prize in the Forum of the XXII Uruguayan Congress of Surgery (December 1971)